Initiation of Blended Learning through Kannada Wikipedia, Issues and Challenges - A Case Study (Global Journal of Human-Social Science, 2018)
Globalization has brought about a lot of technological changes in the field of Higher Education. Digital Learning is one among them. In many Academic Institutions, the medium of Instruction is English, so it continued to be the Language for the Technology enabled Teaching and Learning as well. When Knowledge Creation and Dissemination happen only through English, the Vernacular languages get marginalized. A not exposed to English section of society also gets marginalized. Each civilization has its own knowledge traditions. Due to Colonialism and other reasons, there is a break in this knowledge tradition, and it becomes sectarian. Even though, most of the held researches prove the existence of a local system of Knowledge Production, Preservation, and Dissemination in the vernacular languages, these already marginalized sections have not built their knowledge tradition on a par with the one of English. The Knowledge Acquisition through English and vernacular languages go hand in hand, but there is still a gap. It is the responsibility of the Academics to narrow this gap and to bring in the marginalized sections of the society to be the realm of knowledge. Wikipedia, a revolutionary and democratic source of knowledge has embarked upon creating and strengthening the Vernacular Knowledge Tradition by involving the higher educational institutions. Wikipedia has taken up the responsibility of making available a pile of social and cultural data to the younger generation and the public at large, through the vernacular languages in a digital form.
Keywords: digital learning- higher education- knowledge creation- cu experimentation